MEASUREMENT OF RADON CONCENTRATION IN IRAQI AND IMPORTED CEMENT - R.M., RAMADHAN (University of Thi-Qar Journal of Science, 2019)
The determination of the radon concentration that emitted from one of the important building materials which enter directly in our life, the cement ,is carried out by using Solid State Nuclear Track Detector(SSNTDs).The samples of cement from different origins {Iraq (UM QASER, KOFA, ERBIL,SULAYMANIYAH) cement ,Iranian (SHAHREKORD, BOSHER, SEPAHAN,FARS) cement, Indian(SANGHI, HATHI), cement, Pakistani (EAGLE , CAMEL, FALCON ) cement , Kuwaiti (Kuwait ) cement,K.S.A.( Al-QASEM ) cement and U.A.E. (STAR, SHARJAH ) cement} are collected. The results show thatthe average of maximum value of radon concentration was 37.188 Bq/m³ which emitted from Pakistanicement, and the average minimum value was 28 Bq/m³ which emitted from Iraqi cement. The range of theeffective dose for workers in this field was from 0.1139 mSv/y to 0.2038 mSv/y and to the visitors of thelocations of the production and stores of cement was from 0.0142 mSv/y to 0.0254 mSv/y.